Calcampus: board game - Kamarul Zaman, Mustaqim Syah; Zalhizra, Muhammad Yazdane; Zulkifli, Ahmad Zain; Mohammad Shaharom, Muhammad Azreen; Mahat, Aishah; Makmor, Shafinaz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Welcome to "Calcampus: Board Game," where the world of mathematics and the excitement of Monopoly collide! In this unique board game, players will experience the thrilling world of calculus while strategizing their way to victory. After day and night brainstorming the major problem for students who hates Calculus let alone to open the book. We found that the problem is learning Calculus to them is no fun complicated. Through our research, many students rather playing games than doing practice. So, we came up with solution to help students study and practice calculus while having fun. Who doesn’t like Monopoly? Everyone loves Monopoly, it’s like a tradition game to play alongside your friends, family and relatives. The objective is to make students thrill to learn and practice Calculus through our Invention. Our invention maintains the rules in Monopoly with a slight change to fit our objective. Every question they answered will be rewarded with money. Isn’t it thrilling? Knowledge that will reward you with money. Buy, sell, and trade properties, solve equations to earn rewards, and leverage your mathematical skills to outwit opponents. Are you ready to integrate fun and learning in a game like no other? Let the journey through the world of Calcampus begin!